TANTANGAN DAN SOLUSI PENERAPAN SISTEM INFORMASI AKUNTANSI DI INDONESIA: SEBUAH ANALISIS TEMATIK - Hilia Anriva, Della (Jurnal Akuntansi, 2024)
This research aims to investigate the benefits, obstacles and recommendations for implementing Accounting Information Systems (AIS) in Indonesia. The research method used is qualitative, with data sources from scientific documents such as journals and thematic analysis using NVivo 12 Plus software. This study outlines some of the critical benefits of AIS, including improved operational efficiency, data accuracy, transparency, decision support, and regulatory compliance. However, various barriers were also identified, such as limited technological infrastructure, changes in organizational culture and processes, data security, lack of management understanding and support, and implementation and training costs. Recommendations to overcome these barriers include increasing understanding and awareness of AIS, evaluating technology infrastructure, employee training, and collaboration with professional service providers. These findings highlight the need for better awareness of the benefits of AIS, improved technological infrastructure, employee training, and management support as critical factors in the successful implementation of AIS in Indonesia. Further research is recommended to conduct field studies through interviews and observations to gain deeper insight into the challenges and needs in implementing AIS in Indonesia.